Micro-CT and micro-FE analysis of pedicle screw fixation under different loading conditions. (21st March 2018) - Chevalier, Y.; Matsuura, M.; Krüger, S.; Fleege, C.; Rickert, M.; Rauschmann, M.; Schilling, C.
Abstract: Anchorage of pedicle screw instrumentation in the elderly spine with poor bone quality remains challenging. In this study, micro finite element (µFE) models were used to assess the specific influence of screw design and the relative contribution of local bone density to fixation mechanics. These were created from micro computer tomography (µCT) scans of vertebras implanted with two types of pedicle screws, including a full region-or-interest of 10 mm radius around each screw, as well as submodels for the pedicle and inner trabecular bone of the vertebral body. The local bone volume fraction (BV/TV) calculated from the µCT scans around different regions of the screw (pedicle, inner trabecular region of the vertebral body) were then related to the predicted stiffness in simulated pull-out tests as well as to the experimental pull-out and torsional fixation properties mechanically measured on the corresponding specimens. Results show that predicted stiffness correlated excellently with experimental pull-out strength (R 2 > 0.92, p < .043), better than regional BV/TV alone (R2 = 0.79, p = .003). They also show that correlations between fixation properties and BV/TV were increased when accounting only for the pedicle zone (R 2 = 0.66–0.94, p ≤ .032), but with weaker correlations for torsional loads (R 2 < 0.10). Our analyses highlight the role of local density in the pedicle zone on the fixation stiffness and strength of pedicle screws when pull-out loads are involved, but that local apparent bone density alone may not be sufficient to explain resistance in torsion.